The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1001/archinte.159.14.1582
|View full text |Cite
|
Sign up to set email alerts
|

The Siesta in the Elderly

Abstract: Background: During the siesta, blood pressure declines like it does during night sleep. Because cardiovascular and cerebrovascular events cluster during the morning hours, when hemodynamic changes from nocturnal baseline are maximal, we hypothesized that an additional sleep period during the day (the siesta) may increase cardiovascular and cerebrovascular events, and thus mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(23 citation statements)
references
References 25 publications
2
20
1
Order By: Relevance
“…Because cardiovascular and cerebrovascular events cluster after wakening from night sleep, while changes from nocturnal baseline are maximal, a second peak of such events after an additional sleep period during the day could be hypothesized. Such an association of siesta with an increased risk of myocardial infarction and higher mortality risk due to cardiovascular events, as well as an effect of siesta on parameters of cardiac structure have recently been suggested [32, 33, 34]. To our knowledge, there is no other study directly indicating a relation between siesta and a second temporal peak of stroke occurrence.…”
Section: Discussionmentioning
confidence: 87%
“…Because cardiovascular and cerebrovascular events cluster after wakening from night sleep, while changes from nocturnal baseline are maximal, a second peak of such events after an additional sleep period during the day could be hypothesized. Such an association of siesta with an increased risk of myocardial infarction and higher mortality risk due to cardiovascular events, as well as an effect of siesta on parameters of cardiac structure have recently been suggested [32, 33, 34]. To our knowledge, there is no other study directly indicating a relation between siesta and a second temporal peak of stroke occurrence.…”
Section: Discussionmentioning
confidence: 87%
“…However, in older people, habitual napping may be a risk factor for morbidity and mortality. Bursztyn et al [22] found that the mortality in 70-year-old Jerusalem residents who were in the habit of taking a daytime nap was twice as high as that in residents who were non-nappers, independent of other factors. Many previous cross-sectional studies found an association between day napping and diabetes in elderly populations (>50 years).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, elderly people may be at risk of sudden increased blood pressure upon awakening 17,18) . Self-awakening could be useful, as a means of preventing these sudden increases in heart rate and blood pressure.…”
Section: Introductionmentioning
confidence: 99%